1988
DOI: 10.1101/gad.2.9.1063
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of a Drosophila male accessory gland gene whose product resembles a peptide pheromone precursor.

Abstract: The accessory gland of male insects is a genital tissue that secretes many components of the ejaculatory fluid, some of which affect the female's receptivity to courtship and her rate of oviposition. We have examined the structure and expression of two tightly linked genes that are expressed exclusively in the male accessory glands of adult Drosopbila melanogaster. The two genes are transcribed from the same strand of DNA, and are separated by 20 bases. Both genes are regulated by the sex determination hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 48 publications
1
109
0
Order By: Relevance
“…genetics.org/supplemental/), the majority of which encode proteins with a predicted secretion signal sequence, and all of which show male-biased expression with enrichment either in accessory glands (Monsma and Wolfner 1988;Wolfner et al 1997;Swanson et al 2001;Holloway and Begun 2004;Mueller et al 2005;Walker et al 2006;Chintapalli et al 2007) or in the ejaculatory duct or bulb (Est-6: Ludwig et al 1993;Andropin: Samakovlis et al 1991;Gld: Cavener et al 1986; PEB-ME: Dup99B: Saudan et al 2002). Evolutionary rates of 25 of these 68 seminal protein genes were estimated using the six fully sequenced genomes of the melanogaster species group; orthologs of the other 43 genes either were not identified in one or more species or have undergone gene duplication and were therefore not included.…”
Section: Methodsmentioning
confidence: 99%
“…genetics.org/supplemental/), the majority of which encode proteins with a predicted secretion signal sequence, and all of which show male-biased expression with enrichment either in accessory glands (Monsma and Wolfner 1988;Wolfner et al 1997;Swanson et al 2001;Holloway and Begun 2004;Mueller et al 2005;Walker et al 2006;Chintapalli et al 2007) or in the ejaculatory duct or bulb (Est-6: Ludwig et al 1993;Andropin: Samakovlis et al 1991;Gld: Cavener et al 1986; PEB-ME: Dup99B: Saudan et al 2002). Evolutionary rates of 25 of these 68 seminal protein genes were estimated using the six fully sequenced genomes of the melanogaster species group; orthologs of the other 43 genes either were not identified in one or more species or have undergone gene duplication and were therefore not included.…”
Section: Methodsmentioning
confidence: 99%
“…Hemolymph sample collection and Western blotting were performed as previously described (Lung and Wolfner 1999;Ravi Ram et al 2005). Several other Acps with known patterns of localization were used as controls (ovulin and Acp26Ab, Monsma and Wolfner 1988;Acp76A, Coleman et al 1995;Acp62F, Lung et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence classes of the 83 predicted Acps, isolated in several screens (Schäfer, 1986;DiBenedetto et al, 1987;Chen et al, 1988;Monsma and Wolfner, 1988;Simmerl et al, 1995;Wolfner et al, 1997;Swanson et al, 2001). The sequence and function of the four example Acps are described in: Acp26Aa (Monsma and Wolfner, 1988;Herndon and Wolfner, 1995;Heifetz et al, 2000;Chapman et al, 2001), Acp70A (Chen et al, 1988;Aigaki et al, 1991;Kubli, 1996;Moshitzky et al, 1996;Soller et al, 1997), Acp36DE Neubaum and Wolfner, 1999;Chapman et al, 2000) and Acp62F Lung et al, 2002).…”
Section: Figurementioning
confidence: 99%
“…Early studies involving differential cDNA hybridization screens to identify male-specific RNAs expressed in accessory glands (Schäfer, 1986;DiBenedetto et al, 1987;Monsma and Wolfner, 1988;Simmerl et al, 1995;Wolfner et al, 1997), or (in one case) identification of an accessory gland peptide by a functional assay (Chen et al, 1988), identified 18 Acp genes; according to Drosophila convention, these genes are named 'Acp' followed by the designation of their chromosome position. SDS-PAGE analysis of accessory gland proteins coupled with statistical tests based on the frequency of 'multiple hits' in the cDNA screens suggested that there were about 50-100 different Acps (Chen, 1991;Wolfner et al, 1997).…”
Section: How Arementioning
confidence: 99%